Pengaruh Pendidikan, Pendapatan dan Kepadatan Penduduk Serta Distribusi Pendapatan Terhadap Permintaan Air PDAM di Kabupaten/Kota Provinsi Sumatera Barat - Riska Ratna Dewi Anugrah; Sri Ulfa Sentosa (Universitas Negeri Padang, 2023)
This study aims to examine the effect of Education, Income and PopulationDensity as well as Income Distribution on Water Demand in theRegencies/Cities of West Sumatra Province with the selected model being theRandom Effect Model (REM). The data used is panel data with a cross sectionof 18 regencies/cities and a 5 year time series from 2017 – 2021. The results ofthis study indicate that education has a significant positive effect on PDAMwater demand. The income and population density variables have nosignificant positive effect, while the income distribution variable has nosignificant negative effect on PDAM water demand.